Success of Women Entrepreneurs: An Empirical Study on Indian Women Entrepreneurs - PAL, BRAJABALLAV; MISHRA, SURABHI (International Journal of Psychosocial Rehabilitation, 2024)
This study endeavored to primarily investigate the success factors of small and medium scalewomen run businesses in Kolkata, India. Other crucial objectives of the investigationincluded finding about the challenges faced by these female entrepreneurs, difference inperception of success factors by educated and uneducated women entrepreneurs, and thefactors that compel (push) & motivate (pull) these women to start their own business. Thestudy is exclusively based on primary data collected through a self-administeredquestionnaire filled by over 130 women entrepreneurs. Descriptive statistical tools such aspercentage, frequency, rank order, weighted average and standard deviation were used toanalyze the data. T-test analysis was conducted to analyze the difference between theperception of success factors for educated and uneducated women entrepreneurs. The resultsreveal that women consider personal attributes like skills, business ethics and good customerrelation as the most crucial success factor to a business. Challenges faced are mostly genderbased leading to low self-esteem. Unemployment pushes women into entrepreneurshipwhereas desire for economic independence pulls or motivates them to enter entrepreneurship.